IMPLEMENTATION OF E-MARKETING AS THE EMBODIMENT OF TOURISM 4.0 INDONESIAN SAFARI TOUR - Muhammad Rijwan Jahmi; Syifa Alifia Putri (Sekolah Tinggi Pariwisata Mataram, 2022)
Bogor city tourism has a variety of tourist objects that become tourist attractions' favorite places in local communities and outside the region, especially the tourist attractions of the Indonesian Safari Park. The number of tourist attractions in the city of Bogor has become a distinctive form of Bogor and is widely known to the public, even not a few foreigners come to travel. Tourism is a sector that contributes well to the Indonesian economy. So, it needs a planned and structured tourism development effort to realize the 4.0 tourism industry in Bogor city tourism. Therefore, e-marketing or digital marketing is needed as a form of embodiment. Based on these problems, this study was conducted to explain how to implement e-marketing properly and analyze the tourism potential in the city of Bogor with the application of e-marketing. The research method used is the qualitative research method. Collecting data in this study are visitor distribution data based on information media sources and data on the use of social media as marketing media in 2019. The results of this study can show the effect of the implementation of e-marketing on the realization of tourism 4.0.